The Origin and Characteristics of Islamic Community-Based Enterprise: An Exploratory Case Study in Bandung City - Indra Fajar Alamsyah; Azura Omar (University of Darussalam Gontor, 2022)
Prior research has investigated the role of Islamic values in community-based enterprise. The authors contributed to this line of research by exploring a community-based perspective. Using the resource-based view theory fundamental lens, this study aims to reveal the origins and unique characteristics of Islamic community-based enterprise. This research is an exploratory research with qualitative case study research involving 9 participants, all of whom are founders of a community-based business that uses Islamic principles. This study uses in-depth interview and observation as methods. The results show there are 3 origins of Islamic community-based enterprises, all of which have differences with conventional community-based enterprises. As for the characteristics, there are unique characteristics of Islamic community-based enterprise that are not found in conventional literature. The authors contribute to uncovering new variant of the idea of Islamic entrepreneurship and community. This study reveals the birth of the idea of an Islamic community-based enterprise as a breakthrough concept that integrates entrepreneurship, community functions and Islamic values. This research also opens a form of Islamic entrepreneurship which in previous studies is more prominent in the individual perspective.